2021
DOI: 10.4103/ijd.ijd_71_21
|View full text |Cite
|
Sign up to set email alerts
|

Contact Allergy to Ammonium Persulfate

Abstract: Background: Persulfate is an oxidizing agent used for multiple purposes, including bleaching hair, bleaching flour, and as pool/spa water disinfectant. Objective: To identify the prevalence and clinical characteristics of patients allergic to ammonium persulfate (APS) among patients who underwent patch testing in our clinic. Methods: A retrospective chart review of 2138 patients who underwent patch testing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…2 In a single-center retrospective review of 2138 patients who underwent patch testing at Brigham and Women's Hospital from 2015 to 2019, 61 (2.85%) had 2+ or 3+ patch test reactions to APS. 13 In comparison, the NACDG study reported 0.75% of patients had 2+ or 3+ reactions. 2 Persulfate sensitivity can present as dermatitis of the hands, trunk, or face after exposure to spa water/swimming pools, hair-bleaching products, or disinfectants.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…2 In a single-center retrospective review of 2138 patients who underwent patch testing at Brigham and Women's Hospital from 2015 to 2019, 61 (2.85%) had 2+ or 3+ patch test reactions to APS. 13 In comparison, the NACDG study reported 0.75% of patients had 2+ or 3+ reactions. 2 Persulfate sensitivity can present as dermatitis of the hands, trunk, or face after exposure to spa water/swimming pools, hair-bleaching products, or disinfectants.…”
Section: Discussionmentioning
confidence: 91%
“…In a single‐center retrospective review of 2138 patients who underwent patch testing at Brigham and Women's Hospital from 2015 to 2019, 61 (2.85%) had 2+ or 3+ patch test reactions to APS 13 . In comparison, the NACDG study reported 0.75% of patients had 2+ or 3+ reactions 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ammonium persulfate (APS) is an oxidizing agent used for multiple purposes including bleaching hair and bleaching flour. In 2020, We reviewed the prevalence of ammonium persulfate allergy among 2138 patients who underwent patch testing at Brigham and Women's Hospital in Boston, and we found that 2.85% of our study sample had positive allergic reactions to APS [30]. According to the North American Contact Dermatitis Group patch test study that included 10526 between 2015 to 2018, allergy to APS was found to be 1.8% among patch-tested patients [31].…”
Section: Allergens In Hair Bleachingmentioning
confidence: 90%